Analisis Kemauan Membayar Retribusi Sampah di Kecamatan Lotu Kabupaten Nias Utara - Denomi Kristin Gea; Gita Prajati (Jurnal Serambi Engineering, 2024)
Lotu Subdistrict, located in North Nias Regency, is experiencing a problem in waste retribution cost. The environmental office feels that the amount of waste retribution cost is too small. Meanwhile, the community feels that the waste retribution cost is not comparable to the service. The aims of this research are to know the willingness to pay (WTP), the cost of willingness to pay and also the influencing factors of willingness to pay in the community of Lotu subdistrict. Data were collected by distributing questionnaires to 97 respondents. The data were analysed by Contingent Valuation Method (CVM) to determine the cost of WTP and the total cost of WTP. Besides, the data analysed by multiple regression which is used to determine the influential factors of WTP. This research shows that 21% of respondents are unwilling to pay the cost of waste disposal and 79% of respondents are willing to pay the cost of waste disposal. The average cost of WTP for each household is Rp. 8,207.79 per month. There are two factors that influence WTP, which are gender and age. Whereas income, education, number of family members and employment have no influence on WTP in Lotu subdistrict